2017
DOI: 10.1111/jog.13319
|View full text |Cite
|
Sign up to set email alerts
|

Impact of borderline–subclinical hypothyroidism on subsequent pregnancy outcome in women with unexplained recurrent pregnancy loss

Abstract: Although some subset of uRPL is though to be due to as-yet-unidentified cause(s), borderline-SCH is unlikely to be involved in uRPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…One study reported no significant association between subclinical hypothyroidism and pregnancy loss in women with unexplained recurrent pregnancy loss. In this retrospective study of 317 Japanese women with unexplained recurrent pregnancy loss, Uchida et al found that among women with untreated "borderline" subclinical hypothyroidism, defined as a TSH between 2.5 and 4.5 mIU/L, 29% (9/31) had a subsequent pregnancy loss compared to 17.9% (24/134) of euthyroid controls, P = 0.16 (18).…”
Section: Hypothyroidismmentioning
confidence: 97%
See 1 more Smart Citation
“…One study reported no significant association between subclinical hypothyroidism and pregnancy loss in women with unexplained recurrent pregnancy loss. In this retrospective study of 317 Japanese women with unexplained recurrent pregnancy loss, Uchida et al found that among women with untreated "borderline" subclinical hypothyroidism, defined as a TSH between 2.5 and 4.5 mIU/L, 29% (9/31) had a subsequent pregnancy loss compared to 17.9% (24/134) of euthyroid controls, P = 0.16 (18).…”
Section: Hypothyroidismmentioning
confidence: 97%
“…b) Adverse Outcomes of Subclinical Hypothyroidism (Question 34) "What adverse outcomes are associated with subclinical hypothyroidism during pregnancy?" Ten studies on adverse outcomes in subclinical hypothyroidism have been published in 2017 and 2018 as noted in Table 1 (9)(10)(11)(12)(15)(16)(17)(18)(19)(20)(21). Two studies reported that subclinical hypothyroidism was associated with changes in fetal growth, however, the changes were different between studies (15,16).…”
Section: Hypothyroidismmentioning
confidence: 99%
“…Two studies using a pre‐pregnancy TSH threshold of 2.5 mIU/L found no association with increased miscarriage . To date, three studies have investigated thyroxine replacement in RM patients with SCH diagnosed using TSH >2.5 mIU/L and found no improvement in either miscarriage or live birth.s Also, in a recent large retrospective cohort study involving 5405 pregnant women with SCH, thyroxine replacement was associated with reduced miscarriage only in those with TSH >4 mIU/L and not if TSH was 2.5–4 mIU/L . There are no RCTs examining the impact of thyroxine in RM women with SCH.…”
Section: Endocrine Factors: Thyroid Function Pcos and Prolactinmentioning
confidence: 97%
“…However, in several studies no adverse perinatal outcomes of SH were found [23][24][25][26]. These inconsistent results may be related to a different criteria of SH diagnosing, co-existance of anti-thyroid antibodies which are attributable to be an independent risk factor for pregnancy adverse outcomes, different maternal age of the studied groups and various gestational age of thyroid function evaluation.…”
Section: Introductionmentioning
confidence: 97%